A Novel Electrochemical Sensor for Detection of Molinate Using ZnO Nanoparticles Loaded Carbon Electrode. Issue 6 (28th February 2019) - Shetti, Nagaraj P.; Malode, Shweta J.; Ilager, Davalasab; Raghava Reddy, Kakarla; Shukla, Shyam S.; Aminabhavi, Tejraj M.
Abstract: In this work, electrochemical detection of molinate herbicide was studied by developing a novel sensor based on carbon paste incorporated with zinc oxide (ZnO) nanoparticles using cyclic (CV) and square wave voltammetric (SWV) techniques. Molinate exhibited one well resolved peak at pH of 3.0 phosphate buffer solution (PBS), which was irreversible. The lowest possible detection limit of 1.0×10 −8  M was achieved in the concentration range of 0.002 μM to 0.25 μM. The modifying ability of ZnO nanoparticles was responsible for such a low level sensing in water and soil samples. Abstract :